Literature of Review Influence Work Life Balance, Flexible Working Arrangements, and Organizational Support for Job Satisfaction Online Driver in Bekasi City - Nayla Aqilah; Muhammad Richo Rianto (IJESM Indonesian Journal of Economics and Strategic Management, 2023)
This research aims to determine the effectwork lifebalance (X1),flexible working arrangements (X2),andorganization support (X3) on job satisfaction (Y)ondriver taxibikeonline in Bekasi City. This researchuses quantitative methods, the population in thisresearch is alldriver taxibikeonline in Bekasi City. Andusing primary data which in this research wasobtained by conducting a questionnaire distributedto participantsdriver taxibikeonline which includesGo-jek, Grab, and Maxim.